Complexity and ambition in nurse education. (16th September 2022) - Lipscomb, Martin
Abstract: Panel contribution by Martin Lipscomb to online event "Addressing current debates in nursing theory, education, and practice". Event hosted by the University of California Irvine, in association with the International Philosophy of Nursing Society.